2017
DOI: 10.1158/1055-9965.epi-16-0801
|View full text |Cite
|
Sign up to set email alerts
|

Family History of Breast Cancer, Breast Density, and Breast Cancer Risk in a U.S. Breast Cancer Screening Population

Abstract: Background The utility of incorporating detailed family history into breast cancer risk prediction hinges on its independent contribution to breast cancer risk. We evaluated associations between detailed family history and breast cancer risk while accounting for breast density. Methods We followed 222,019 participants aged 35–74 in the Breast Cancer Surveillance Consortium, of whom 2,456 developed invasive breast cancer. We calculated standardized breast cancer risks within joint strata of breast density and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 28 publications
(38 reference statements)
4
31
0
Order By: Relevance
“…We also found that patient with a family history of breast carcinoma in first degree relatives has increased risk of breast cancer. This finding is in line with the previous reports from other studies from India and abroad [ 14 15 16 ]. Atypical hyperplasia is a premalignant condition for breast carcinoma and leads to an increased incidence of breast cancer.…”
Section: Discussionsupporting
confidence: 94%
“…We also found that patient with a family history of breast carcinoma in first degree relatives has increased risk of breast cancer. This finding is in line with the previous reports from other studies from India and abroad [ 14 15 16 ]. Atypical hyperplasia is a premalignant condition for breast carcinoma and leads to an increased incidence of breast cancer.…”
Section: Discussionsupporting
confidence: 94%
“…As shown in Table 3, the hypertension was not associated with breast cancer risk. Our data is consistent with studies conducted by Wang et al [61] and Sun et al [62]. One cohort study, one nested case-control study and ten case-control studies showed that hypertension is associated with increased risk of breast cancer [63].…”
Section: Discussionsupporting
confidence: 93%
“…Family history is an important risk factor for breast cancer, a disease that accounts for approximately 25% of all cancers diagnosed in women . Approximately 15% of all breast cancers are diagnosed among women with a family history of the disease . Women with a family history of breast cancer are at a 2 to 4 times increased risk of breast cancer depending on the number of affected relatives and the age at which the relatives were diagnosed .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the majority of studies assessing the familial risk of cancers, including breast cancer, take family history as a marker of familial predisposition, and as constant during the lifetime of an individual. Common approaches that are used to assign family history status include having at least 1 affected first‐degree relative (FDR), the number and type of affected FDRs, or a detailed combination of FDRs and second‐degree relatives (SDRs) . In register‐based studies, family history often has been assessed and assigned (as a static variable) at a single point in time, typically at the end of follow‐up, an approach that does not take into account the timing of events .…”
Section: Introductionmentioning
confidence: 99%